Using web-based activities to promote reading: an exploratory study with teenagers (2012)
It is considered valuable to take advantage of web activities to improve and qualify the English teaching and learning processes, especially in the promotion of reading comprehension. In this article we share the process and results of a study that focused on some activities based on web materials that were designed and used with 10th grade students, with the purpose of promoting reading. Data was gathered through the use of questionnaires, surveys and web activities. The results showed that most of thestudents agree on the fact that reading more information concerning a specific topic or about different subjects makes them work with enthusiasm; they also had new possibilities to access knowledge in a different way and to improve reading comprehension.Se considera valioso tomar ventaja de las actividades basadas en materiales web para mejorar y cualificar los procesos de la enseñanza y aprendizaje del idioma inglés, especialmente en la promoción de la comprensión lectora. En este artículo compartimos los procesos y resultados de un estudio que se centró en algunas actividades basadas en materiales web que fueron diseñadas y empleadas porestudiantes de décimo grado con el propósito de promover la lectura. La información se recogió mediante cuestionarios, encuestas y materiales web. Los resultados mostraron que la mayoría de los estudiantes están de acuerdo con que leer información concerniente a un tema específico o de diferentes materias los puede motivar a trabajar con entusiasmo y que también tienen nuevas posibilidades paraacceder al conocimiento de una manera diferente y mejorar su comprensión lectora